ANALISIS KUALITAS LINGKUNGAN HIDUP TERHADAP KESEHATAN MASYARAKAT DI AREA PELABUHAN BUNATI PT. BORNEO INDOBARA KABUPATEN TANAH BUMBU - Vina Delya; Syarifuddin Kadir; Badaruddin Badaruddin; Gusti Rusmayadi (EnviroScienteae, 2023)
The research was conducted in Bunati Village which is located in Tanah Bumbu Regency. The research method used is quantitative. Data collection was carried out by measuring the levels of TSP, CO, and Fe in clean water at 3 research locations in Bunati Village and measuring public health using a respiratory disorder questionnaire, a skin disease questionnaire, and peripheral oxygen saturation. The results of the analysis of the levels of TSP, CO, and Fe in clean water at 3 research location points showed that they were below the environmental quality standards with TSP values (µg/Nm3) : (1) 38 (II) 41 (III) 77, CO (ppm): 115, and Fe of clean water (mg/L): 0.018. The results of the respiratory disorder questionnaire showed that an average of 67.74% of the people indicated respiratory problems, while for SpO2 the average community was 97.4% and for complaints related to skin diseases from 93 respondents there were no people who complained of skin diseases. Pearson correlation test results between TSP levels and respiratory disorders are above the value of α (0.061), which means there is no relationship between TSP levels and respiratory disorders, as well as CO and SpO2 as well as Fe levels in well water and skin disorders also show no results. significant relationship. An alternative solution to the problem that can be done is the company can use technology such as Automatic Water Sprinkle by installing HDPE pipes in the Port concession area.This study concluded that the results of the analysis of the quality of the environment in Bunati Village indicated that it was in good condition. Based on the results of measurements of TSP, CO, and Fe in water all are still below environmental quality standards, which means that the coal port activity has no significant impact on the environment and the people of Bunati Village.